(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
In densely populated tropical urban contexts, row houses (RD) have increasingly emerged as a prevalent residential solution owing to their efficiency in land utilization and economic affordability. Nevertheless, the compact and contiguous spatial configuration characteristic of this housing typology significantly restricts the availability of natural ventilation openings, impedes effective cross ventilation, and consequently reduces levels of thermal comfort and indoor air quality. Under such conditions, occupants tend to rely more heavily on mechanical ventilation systems, which in turn leads to increased energy consumption and a decline in overall environmental sustainability. This study explores the potential role of staircases as vertical void elements capable of enhancing natural ventilation performance through the application of the stack effect mechanism. An experimental investigation was carried out to analyze the influence of sixteen combinations derived from variations in staircase geometry (I, L, U, ?, and their mirrored configurations), tread construction (solid and perforated), and staircase placement (front, center, and rear) on natural ventilation performance within row house typologies. A quantitative research approach was adopted through the application of Computational Fluid Dynamics (CFD) simulations to evaluate airflow behavior and thermal conditions. The findings indicate that staircases with a massive U-shaped construction geometry demonstrate the most optimal natural ventilation performance, achieving an air velocity of 5 m/s and a temperature of 33.5°C. Specifically, within the U-shaped staircase configuration, airflow velocity increased from stagnant conditions to an active state, reaching 4.62 m/s, accompanied by a temperature reduction of approximately 1°C. These results emphasize the significance of staircases as effective passive design components and underscore their potential contribution to improving energy efficiency and promoting sustainability in tropical urban residential architecture.